2013
DOI: 10.2169/internalmedicine.52.8437
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Osteomyelitis in the Ulna of a Patient Undergoing Hemodialysis

Abstract: A 76-year-old woman on hemodialysis (HD) presented with pain and swelling in the left wrist and forearm. The osteomyelitis occurred in the part of the ulna adjacent to the arteriovenous fistula. Mycobacterium tuberculosis was identified in pus obtained from the left forearm, leading to a diagnosis of tuberculous osteomyelitis. The patient was treated with anti-tuberculous drugs and her symptoms improved. In this study, we report a case of tuberculous osteomyelitis occurring in the ulna, which is not the usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…It was found to be 6–25 times higher than in the general population, with mortality rates ranging from 17 to 75% [6]. Ates et al [8] reported that the median time between initiation of dialysis and diagnosis of TB was 11 months, which is consistent with several studies showing a high incidence of TB in the first year of dialysis attributable to poor health in general and compromised host immunity.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It was found to be 6–25 times higher than in the general population, with mortality rates ranging from 17 to 75% [6]. Ates et al [8] reported that the median time between initiation of dialysis and diagnosis of TB was 11 months, which is consistent with several studies showing a high incidence of TB in the first year of dialysis attributable to poor health in general and compromised host immunity.…”
Section: Discussionsupporting
confidence: 58%
“…There are many known risk factors for TB infection, e.g., age, malnutrition, HIV infection, diabetes mellitus, transplantation, malignancy, and low socioeconomic status [5]. Advanced chronic kidney disease is also one of the risk factors due to impaired immune function secondary to oxidative stress and inflammation, 25-hydroxyvitamin D deficiency, malnutrition, anemia, and hyperparathyroidism [1, 6]. It seems clear that lymphopenia, suboptimal responses to mitogens, abnormal cytokine gene expression, and abnormal IL-2R expression are seen in a number of dialysis patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentations of extrapulmonary tuberculosis should be considered in the differential diagnosis of many infectious and noninfectious diseases (15). It can cause acute conditions such as meningitis and endocarditis, which have high morbidity and mortality rates, as well as infections with delayed diagnoses such as chronic osteomyelitis (16)(17)(18). In a study conducted in Turkey, tuberculosis was found to be the most common cause of infectious reasons for fever of unknown origin (19).…”
Section: Discussionmentioning
confidence: 99%
“…The culture from the wound swab was regarded as a red herring. According to Nakazawa et al, 1 he and his team took 6 months to reach a diagnosis of tuberculous osteomyelitis reflecting the level of difficulty in differentiating tuberculous osteomyelitis from bacterial osteomyelitis or bone tumours. The mean interval between the first symptoms and the diagnosis was 26.4 months (range 1 month to 15 years).…”
Section: Discussionmentioning
confidence: 99%